A Parade of Adornments (Isa 3:18–23): Daughters Zion in the Light of Gender and Material Culture Studies - Létourneau, Anne (Open theology, 2022)
This article investigates the list of items of dress worn by the daughters Zion in Isa 3:18-23, as they are simultaneously stripped of them. It considers the poetic aspects of this list before turning to specific items, both jewelry and clothing, worn by the daughters in verses 18 and 22. These objects contribute to the complex characterization of the daughters Zion, as it poetically brings together a thick array of aesthetic, religious and traumatic meanings, and experiences.